Analisis Pengembangan Desain pada Kemasan Produk dengan Menggunakan Metode Quality Function Deployment pada UMKM Kerupuk Subur - Tegar Adhe N. F; Zanuar Ilham Mahendra; Khibran Nur Kartiko; Rizky Subekti Anam; Suseno Suseno (International Forum of Researchers and Lecturers, 2026)
UMKM Kerupuk Subur is one of the SMEs quite well-known for its cracker products and is located at Jl. Gedongkuning Gg. Nuri No.66, RT.2/RW.33, Wonocatur, Banguntapan, Bantul Regency, Special Region of Yogyakarta. Product packaging is one of the important factors in maintaining the quality of the crackers to keep them crispy and not easily soggy. Currently, UMKM Kerupuk Subur still uses ordinary plastic packaging that is only tied with a string, so its protection against physical damage and product quality deterioration is still limited. Besides functioning as a protector, product packaging also serves as a consumer attraction that can influence purchasing decisions. In 2024, UMKM Kerupuk Subur experienced a production and sales decline of 4.58 percent, which is suspected to be influenced by packaging factors. This study aims to develop Kerupuk Subur packaging based on customer criteria and needs. The Green Quality Function Deployment approach is used to obtain comprehensive information in designing packaging according to consumer needs and preferences. The results of identifying consumer needs show priorities such as packaging that is easy to open, resealable, transparent, environmentally friendly, durable, and tear-resistant. Based on these needs, packaging development alternatives were designed, including an easy-open system, durable and tear-resistant packaging, and resealable packaging to maintain product quality and crispness. Then, testing was conducted with 50 respondents to assess consumer satisfaction. The level of consumer satisfaction falls into the satisfied category, with an average score of 4.18, where 80% of respondents stated they were satisfied or very satisfied with the designed packaging prototype.